Tell Barri / Kahat. La campagna del 2004 - Pecorella, Paolo Emilio (Strumenti per la didattica e la ricerca, 2008)
In the undulating plains of north-eastern Syria is the site of Tell Barri, identified with the city of Kahat. The archaeological sequence which has been brought to light stretches without interruption from the start of the third millennium up to the fourteenth century AD. This report illustrates the results of the twentieth excavation campaign, carried out by the group from the University of Florence and from the "Federico II" University of Naples. In Area G the levels of the first half of the III millennium BC and a sequence of strata of the Mitanni epoch were investigated, while on the western border of the site another section of the palace of Adad-nirari I was brought to light. In Area J the operations exposed the eastward extension of the palace structure resulting from transformations in the Neo-Babylonian period; in the northern section another courtyard of the palace of Tukulti Ninurta II was brought to light. The text, prepared for printing in July 2005, was published following the tragic death of Paolo Emilio Pecorella, which took place on 29 August in Tell Barri in the course of the excavation campaign.